Market analysis and use of biocides in veterinary clinics of Ukraine - O. M. Lysak; R. A. Peleno (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
Disinfection is key to ensuring the effective operation of veterinary clinics and minimizing the risk of spreading infections. The health of animals undergoing treatment and the biological safety of staff and visitors depends on the quality of disinfection measures. The effectiveness of sanitary treatment of veterinary facilities directly depends on the effectiveness of disinfectants used for its implementation. The work aimed to analyze the market of veterinary biocides in Ukraine and compile a list of the most commonly used for disinfection of veterinary clinic facilities. According to the research results, it was found that from 2020 to 2024, the market of veterinary medicines and biocides in Ukraine experienced significant fluctuations. In particular, the largest number of registrations of veterinary drugs (299) and biocides (90) was recorded in 2020. In 2021, a sharp decrease in registrations was noted, especially for biocides, for which 41.1 % fewer registration certificates were issued than the previous year. In 2022, a temporary increase in the issuance of registration certificates was established due to the registrations of 17 more drugs and 35 more biocides. In 2024, the number of registration certificates issued, compared to the previous year, was 6 fewer for drugs and 13 more for biocides. The increase in the number of registration certificates for biocides after 2021 was due to the registration of more insect-acaricidal agents against the background of a decrease in the registration of technical and antiseptic agents. Thus, among all registered products of this group, the number of registration documents issued for insect-acaricidal products in different years ranged from 66 to 94.7 %, and for technical products decreased from 20 % in 2020 to 5.3 % in 2024. The share for antiseptic products was only in 2020 and 2022 and amounted to 5.0 and 18.4 %, respectively. Similar dynamics were observed in the process of re-registration of biocides. A clear trend was established towards an increase in the share of insect-acaricidal products (from 66 % to 81.6 %), a gradual decrease in the share of technical products, and a small number of antiseptic products (8.2–14 %). It was determined that with a difference of 16.2 %, domestic manufacturers' products prevail in the market of our country, and in the list of the most used for disinfection of veterinary clinic facilities, products containing more than two active substances account for 25 %, based on alcohols, quaternary ammonium compounds and oxidants – 16.6 % each, halogen-containing – 12.6 %, and based on aldehydes, phenols and alkalis – 4.2 %.